Clinical application of mechanical ventilation - Chang, David W. (Delmar Publishers, 2006)
This Workbook is designed to reinforce the essential concepts presented in Clinical Application of Mechanical Ventilation, and give learners practice with questions written in NRBC format. With a concise and easy-to-read approach, the new edition of this book integrates the essential concepts of respiratory physiology with the clinical application of mechanical ventilation. Extensive coverage of airway management and weaning criteria, and a concise view of pharmacotherapy for mechanical ventilation are included. This edition features new material on special procedures in mechanical ventilation, chest tubes and placement, proportional pressure support, airway management, and ventilator waveform analysis